Effects of gender roles, child wish motives, subjective well-being, and marital adjustment on infertility-related stress: a preliminary study with a Hungarian sample of involuntary childless men and women - Cserepes, Réka Eszter; Kollár, János; Sápy, Tamás; Wischmann, Tewes; Bugán, Antal (Archives of gynecology and obstetrics, 2013)
The aim of the study is to investigate the infertility-related stress in a Hungarian infertile population and examine the effects of gender roles, child wish motives, subjective well-being, and marital relationship on the experience of infertility according to our self-constructed conceptual framework.
Gesehen am 28.05.2021